2005
DOI: 10.5902/198050981788
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização florística, fitossociológica e regeneração natural do sub-bosque da reserva genética florestal Tamanduá, DF.

Abstract: O presente trabalho, desenvolvido na Reserva Genética Florestal Tamanduá, DF, teve como objetivo efetuar o levantamento fitossociológico, composição florística e distribuição espacial dos indivíduos das espécies arbóreas ocorrentes no sub-bosque da Reserva, focalizando Cariniana estrellensis (Raddi) O. Kuntze, Apuleia leiocarpa (Vogel) J. F.Macbr., Copaifera langsdorffii Desf., Anadenanthera macrocarpa (Benth.) Brenan, Virola sebifera Aubl., Hymenaea courbaril var. stilbocarpa (Hayne) Lee & Lang., Aspidosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(2 reference statements)
0
2
0
2
Order By: Relevance
“…The Shannon diversity index, both for the total sample and for each individual plot except for Group 3, may be considered high compared with other studies on regenerating strata, such as those of Silva et al (2004) and Oliveira & Felfili (2005) who respectively found diversity indices of 2.89 and 3.02 in central Brazil. The distribution of individuals among species as described by Pielou's evenness calculation (J9 5 0.81) indicated that, in all probability, there is no concentration of the abundance of any species, which indicates the absence of ecological dominance (Dalanesi et al, 2004).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The Shannon diversity index, both for the total sample and for each individual plot except for Group 3, may be considered high compared with other studies on regenerating strata, such as those of Silva et al (2004) and Oliveira & Felfili (2005) who respectively found diversity indices of 2.89 and 3.02 in central Brazil. The distribution of individuals among species as described by Pielou's evenness calculation (J9 5 0.81) indicated that, in all probability, there is no concentration of the abundance of any species, which indicates the absence of ecological dominance (Dalanesi et al, 2004).…”
Section: Discussionmentioning
confidence: 54%
“…The floristic composition of the regenerating stratum of the riparian vegetation of the Pandeiros River showed some similarities to other Brazilian riparian forests and to the tree stratum sampled in the same area. The families Fabaceae, Rubiaceae, Sapindaceae and Myrtaceae were also important in a survey of natural forest regeneration in the Tamandua ´Forest Reserve in the Federal District (Silva et al, 2004), and the families Fabaceae, Anacardiaceae and Bignoniaceae were also the most representative of the tree stratum in that study area (Rodrigues et al, 2009). The species Zygia latifolia and Butia capitata, which have the first and third positions in order of importance (IVI) respectively, are normally found in very wet areas in Brazil (Lorenzi et al, 2004;Nunes et al, 2007), and Tapirira guianensis (second position) is considered a generalist (Oliveira-Filho & Ratter, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al (2004), para mata de galeria semidecidual, encontraram 2,89. Martins et al (2008), avaliando a vegetação de Floresta Estacional Semidecidual em Minas Gerais, considerando indivíduos acima de 1,00 m e DAP ≤ 5 cm, encontraram diversidade variando entre 1,39 e 3,01 no entorno de clareiras e de 1,02 a 3,01 dentro das clareiras.…”
Section: Composição Florística E Estrutura Da Regeneraçãounclassified
“…& Frodin ocorre em diferentes tipologias florestais, como em florestas altas e densas de terra firme, capoeiras, capoeirões, margens de estradas e savanas em quase todo território brasileiro, exceto nos estados do Piauí e Tocantins (CARVALHO, 2003;OHASHI e LEÃO, 2005). Com distribuição espacial ampla, apresenta baixa frequência de indivíduos nos locais de ocorrência (FRANCO e FERREIRA, 2002;SILVA et al, 2004), entre 14 e 39 indivíduos por ha -1 (SILVA et al, 2004;BRAGA e REZENDE, 2007;GIEHL et al, 2007), mesmo com abundante quantidade de frutos e sementes produzidas anualmente (FRANCO e FERREIRA, 2002).…”
Section: Introductionunclassified